PENDEKATAN WHOLE OF GOVERNMENT DALAM PELAYANAN PUBLIK DI MAL PELAYANAN PUBLIK KABUPATEN BATANG - Hibatullah, Mohamad Naufal; -, Fitriyah -; Marlina, Neny - (Journal of Politic and Government Studies, 2024)
The Batang Regency Government is one of the regions that is able to implement the Public Service Mall policy as a real form of collaborative government. The collaboration process involves various parties such as OPD, both vertical and horizontal. The Batang Regency Government is able to implement the Public Service Mall well as proven by the results of previous research, achievements and achievements that have been achieved. This research is aimed at explaining the implementation of Whole of Government in licensing services, as well as analyzing what are the obstacles and incentives for implementing Whole of Government in the Batang Regency Public Service Mall using Sudrajat's theory, namely the application of the Whole of Government approach with 4 (four) indicators, and challenges general in implementing Whole of Government with 3 (three) indicators. This research uses qualitative research methods with a case study approach. The information and data obtained were obtained through interviews and documentation. Apart from that, to support the research results, this research also uses literature studies through newspapers, scientific journals, and the internet and important documents that support the research. The selection of informants used purposive sampling technique. The data analysis techniques in this research involve organizing data, identifying, presenting data and drawing conclusions. The results of this research show that the implementation of the Whole of Government approach in the Batang Regency Public Service Mall is based on seven indicators that can influence the success of implementing the Whole of Government approach, there are five indicators that have been implemented well and there are two indicators that have not been implemented well. The five indicators that have been implemented well and are also driving factors for the implementation of Whole of Government are strengthening coordination between institutions, social coalitions, human and institutional resource capacity, cultural and organizational values, and leadership. Meanwhile, two factors that have not been implemented properly and are also inhibiting factors in implementing Whole of Government are the absence of a special coordinating institution and task force to assist the coordination process. The implementation of the Whole of Government approach in the Batang Regency Public Service Mall shows that not all indicators of good public service can be met, so it is not yet optimal. In general, DPMPTSP as the coordinator of Public Service Mall organizers has been able to carry out in accordance with the indicators according to Sudrajat's theory. Regarding the shortcomings found, the author recommends a suggestion, namely that in the future the coordinator can form a special coordinating institution and task force as a permanent system in establishing and maintaining coordination with agencies in the Batang Regency Public Service Mall